2010
DOI: 10.3109/10428194.2010.512966
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism of leukemia cells: glycolysisversusoxidative phosphorylation

Abstract: For generation of energy, cancer cells utilize glycolysis more vigorously than oxidative phosphorylation in mitochondria (Warburg effect). We examined the energy metabolism of four leukemia cell lines by using glycolysis inhibitor, 2-deoxy-d-glucose (2-DG) and inhibitor of oxidative phosphorylation, oligomycin. NB4 was relatively sensitive to 2-DG (IC(50): 5.75 mM), consumed more glucose and produced more lactate (waste product of glycolysis) than the three other cell lines. Consequently, NB4 was considered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 22 publications
6
94
1
2
Order By: Relevance
“…Regarding the energetic metabolism, our results categorize the different AML cells with NB‐4 as a glycolytic cell line, as reported in some studies,49, 50, 51 HL‐60 cells mainly dependent on glycolysis12 and KG‐1 cells displaying a predominant OXPHOS metabolism. These results not only showed that 2 closely related cell lines, NB‐4 and HL‐60, present different energetic metabolism, but also that KG‐1 cells are mainly OXPHOS dependent, as reflected by the carbon flux through mitochondria for lactate production (Figure 1).…”
Section: Discussionsupporting
confidence: 80%
“…Regarding the energetic metabolism, our results categorize the different AML cells with NB‐4 as a glycolytic cell line, as reported in some studies,49, 50, 51 HL‐60 cells mainly dependent on glycolysis12 and KG‐1 cells displaying a predominant OXPHOS metabolism. These results not only showed that 2 closely related cell lines, NB‐4 and HL‐60, present different energetic metabolism, but also that KG‐1 cells are mainly OXPHOS dependent, as reflected by the carbon flux through mitochondria for lactate production (Figure 1).…”
Section: Discussionsupporting
confidence: 80%
“…In these studies, a great deal of nucleotide alterations were detected in the D-loop region in acute myeloblastic leukemia and myelodysplastic syndrome patients, suggesting that the D-loop is a mutational hotspot in human cancer. It was found that leukemia cells utilize glycolysis more vigorously than oxidative phosphorylation in mitochondria (Gattermann, 2000;Shin et al, 2003;Grist et al, 2004;Suganuma et al, 2010). This may be caused by differences between benign and malignant hematologic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that 2-DG treatment activates AMPK in THP-1 cells (13), which may explain the replenishment of the TCA cycle by fatty acid oxidation by carnitine palmitoyltransferase. Then, the combination of 2-DG and inhibition of AMPK by compound C potently suppressed the growth of THP-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%